Analysis of Noise Distribution from Take-Off and Landing Activities at Haluoleo Airport, Kendari - La Ode Muhamad Nurrakhmad Arsyad; Ranno Marlany Rachman (Jurnal Ilmu Lingkungan, 2025)
Halu Oleo Airport, formerly known as Wolter Mongisidi Airport, is located in Ambaipua Village, Ranomeeto District, South Konawe Regency, Southeast Sulawesi, and serves national flights with a total of 3,103 arrivals and 3,098 departures in 2023. The high flight activity increases noise pressure, impacting public health and the comfort of the surrounding environment. This study analyses the noise level and distribution around Halu Oleo Airport, Kendari, due to landing and take-off activities using the Weighted Equivalent Continuous Perceived Noise Level (WECPNL) index. The method used is descriptive quantitative, with contour simulation based on ArcGIS software. This study measured noise in three locations: runway, taxiway, and apron areas with an average WECPNL of 183.63 dB(A) (zone III/high); airport terminal with an average WECPNL of 76.80 dB(A) (zone II/moderate); and BTN Khalifa Resident area with an average WECPNL of 67.83 dB(A) (zone I/low). Based on the Decree of the Minister of Environment No. Kep.48/MENLH/11/1996, the noise level in the airport area (60 dB(A)) and settlements (55 dB(A)) exceeded the permitted threshold. Contour simulation shows that Zone III is only suitable for airport facilities; Zone II is still used for certain activities even though it violates regulations. Zone I can also be used for various activities, except in school buildings and hospitals. This study concludes that noise around Halu Oleo Airport requires better management to protect the community and the environment.